2018
DOI: 10.1016/j.enpol.2018.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of solar and wind energy: The roles of carbon pricing and aggregate policy support

Abstract: This paper analyzes the roles of policies and preferences in national adoption of solar and wind energy technologies. We use cross-sectional and panel regressions for both the European Union and a broader international sample. We find that countries that price carbon emissions have gone on to adopt more solar and wind energy. The aggregate level of policy support, measured in euros per megawatt hour, appears to have been important for solar energy adoption. We also find that solar energy adoption has been larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 51 publications
(46 reference statements)
0
30
0
1
Order By: Relevance
“…Home energy efficiency labelling in California has been assessed more favourably (Kahn and Kok, 2014). Best and Burke (2018) pursued cross-country analysis, finding that carbon pricing is associated with faster uptake of solar power. Many studies do not empirically assess policy cost-effectiveness.…”
Section: Contributionsmentioning
confidence: 99%
“…Home energy efficiency labelling in California has been assessed more favourably (Kahn and Kok, 2014). Best and Burke (2018) pursued cross-country analysis, finding that carbon pricing is associated with faster uptake of solar power. Many studies do not empirically assess policy cost-effectiveness.…”
Section: Contributionsmentioning
confidence: 99%
“…Kwan () found a positive effect of median home value on solar PV uptake in the United States, while De Groote et al () found mixed results using cadastral income as a proxy for home value in Belgium. Financial capital has also been revealed to be an important determinant of solar use at the national level (Best ; Best and Burke ). A common challenge for incorporating wealth or capital variables is the availability of suitable household‐level datasets.…”
Section: Introductionmentioning
confidence: 98%
“…Detailed information of the solution, as well as extensive results collected in Spanish PV power plants connected to the grid, are also included in the paper. Energies 2018, 11, 3051 2 of 20Best et al [5] affirms that solar and wind resources are on the upper rungs of the energy ladder, their integration being predominant in higher-income countries. Recent contributions, focused on future electricity systems, also assume that renewable assets can be considered a mix between wind-and solar-power generation [6].…”
mentioning
confidence: 99%